Проблеми інтеграції сонячних електростанцій та систем зберігання електроенергії у розподільні мережі - Галько, Сергій Віталійович; Halko, Serhii; Оберемок, Д. О.; Oberemok, D.; Миргород, Д. Г.; Myrgorod, D.; Оксенич, Р. В.; Oksenych, R.; Тоберт, О. Ю.; Tobert, O. (Запоріжжя: ТДАТУ, 2025)
UA: У статті досліджуються ключові проблеми та перспективи розвитку енергетичного сектору в умовах зростання споживання електроенергії та необхідності підвищення його стійкості. Особливу увагу приділено нестабільності генерації з відновлюваних джерел, зокрема сонячних та вітрових електростан-цій, що зумовлює потребу у створенні резервних потужностей та впровадженні систем накопичення енергії. Розглянуто роль акумуляторних систем у балансуванні навантажень та підтриманні стабільності мережі, а також значення технологій Smart Grid для ефективного управління потоками енергії. Показано, що сонячні електростанції завдяки інверторам здатні не лише виробляти активну потужність, а й компенсувати реактив-ну, зменшуючи втрати та підвищуючи ефективність роботи електромереж. Зроблено висновок, що інтеграція інноваційних рішень, таких як системи накопичення, цифровізація управління та оптимізація виробництва, є важливою умовою підвищення надійності, економічності та екологічності сучасних енергетичних систем. /// EN: The article addresses the pressing challenges and future prospects of the power sector in the context of increasing electricity consumption, regional and temporal demand imbalances, and the rapid expansion of renewable energy. Traditional coal- and nuclear-based power plants lack flexibility for frequent power adjustments, which negatively affects equipment life cycle and operational costs. At the same time, solar and wind generation depend on weather and time of day, often misaligned with consumer demand. This creates a need for advanced modeling of generation capacity development, including the integration of demand-side management, energy efficiency measures, and storage technologies. The study emphasizes the importance of energy storage systems, particularly battery energy storage (BESS), which offer instant response, enhance network stability, support frequency regulation, and improve voltage profiles in distributed grids. The paper also highlights recent progress in Ukraine, where renewable integration is gaining momentum despite large-scale destruction of traditional power infrastructure during 2022–2024, driving investments into alternative sources. Economic mechanisms such as the «green tariff» further stimulate solar energy, which already accounts for about 60% of the renewable market. Special attention is devoted to the dual role of solar power plants: in addition to generating active power, their inverters can compensate reactive power, reducing energy losses, lowering costs, and enhancing overall system reliability. The paper explores scenarios involving smart grids, artificial intelligence for predictive load balancing, and distributed generation through local energy systems. Case studies, including Tesla’s 100 MW/129 MWh BESS and Ukraine’s first operational 1 MW storage plant, demonstrate practical applications and benefits. The research concludes that integrating storage, smart grid technologies, and reactive power compensation by PV inverters is a critical step toward building resilient, efficient, and environmentally sustainable power systems capable of addressing both technical and economic challenges.
Problems of integration of solar power plants and energy storage systems into distribution networks
Keywords: відновлювальна енергетика; електрична мережа; відновлювані джерела енергії; сонячні панелі; акумуляторні батареї; генерація; стабільність енергосистеми; енергоефективність; electrical grid; renewable energy sources; solar panels; batteries; generation; power system stability; renewable energy